Метод визначення параметрів синусоїдальних відбивачів інфрачервоних обігрівачів - Максимова, М. О. (НТУ "ХПІ", 2013)
The method of determining of rational parameters of the form and location of sinusoidal infra-red reflectors with the beforehand set properties for heating technical and technological objects are obtained. The algorithms of modeling of motion of reflected rays are created to be able to control the intensity of thermal stream.
Keywords: випромінювання теплове; поток тепловий; інтенсивність; параметри раціональні; моделювання; алгоритм